Subiektywizm i problemy egzystencjalne w "Zapiskach Maltego Lauridsa Brigge" Reinera Marii Rilkego oraz w "Godzinie prawdziwych odczuć" Petera Handkego - Majcher, Piotr (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
This article analyses The Notebooks of Malte Laurids Brigge (1910) by Rainer Maria Rilke and A Moment of True Feeling (1975) by Peter Handke, aiming to demonstrate that the protagonists of the two works are trying to overcome existential problems through the subjectivist perception of reality. The article demonstrates how Rilke and Handke referred to subjectivity in their works listed above. The comparison of The Notebooks of Malte Laurids Brigge and A Moment of True Feeling reveals Handke’s attitude to the concept proposed by Rilke.